There is no Such Thing as a Free Market - Dirk van den Heuvel (Footprint)
To deconstruct the still hegemonic narrative of free market ideologists in the realm of housing, this article looks at the provocative position of the German-British architect Patrik Schumacher, director of Zaha Hadid Architects. Schumacher’s 2016 lecture on housing at the World Architecture Festival in Berlin, in which he claims that only wholesale privatisation of urbanism would solve the housing crisis, is scrutinised on the two interrelated concepts of the free market and state intervention.